Development and Translation of Therapies for Spinal Muscular Atrophy - Hannah K. Shorrock; Thomas H. Gillingwater (European Medical Journal Neurology, 2016)
Spinal muscular atrophy (SMA) is an autosomal recessive neuromuscular disorder characterised by widespread loss of lower motor neurons from the spinal cord, leading to progressive weakness and muscle atrophy. SMA is largely caused by homozygous loss of the survival motor neuron (SMN) 1 gene, resulting in reduced levels of full-length SMN protein. Although no approved treatment is currently available for SMA, several clinical trials investigating different approaches to increase SMN levels are showing promising early results. Trials investigating the use of therapies targeting muscle strength and neuroprotective pathways are also in progress, generating the possibility of delivering combination therapies utilising both SMN-dependent and SMN-independent targets. Due to an increased understanding of the cellular and molecular consequences of SMN depletion, a second wave of therapies targeted at pathways downstream of SMN are currently undergoing preclinical development. As these therapies move forward towards the clinic, new treatment options are likely to become available, raising the potential to generate an effective ‘cure’ for SMA.